The Effect of Foreign Stock Ownership, Quality of Internal Information, and CEO Publicity on Tax Avoidance - Annisa Annisa; Ria Nelly Sari; Vince Ratnawati (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2020)
This research aims to examine and analyze the effect of foreign stock ownership, the quality of internal information, and CEO publicity towards tax avoidance and independent commissioner and audit committee as moderation variables. The research population were manufacture companies listed in Indonesia Stock Exchange periode 2016 until 2018, the number of samples were 192. The technique of taking the samples was by using purposive sampling method by taking samples determined based on certain criteria. Data analysis was conducted by using multiple linear regression model and moderation regression analysis with the assistance of SPSS 23.0 version software. The research results show that foreign stock ownership, the quality of internal information, and CEO publicity has significant effect towards tax avoidance. The result of regression test on moderation variable shows that independent commissioner and audit committee are not moderation variables.